2012
DOI: 10.3390/ijerph9030674
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Smoking and Related Risk Factors among Physical Education and Sports School Students at Istanbul University

Abstract: The purpose of this study was to evaluate smoking prevalence and factors associated with smoking among students at the Physical Education and Sports School of Istanbul University. A cross-sectional study was performed on total of 373 students who have been continuing their education at the school from February to March 2011. A total of 166 responders were male (44.5%) and 207 responders were female (55.5%) out of 373 participants. Of the 373 students, 94 (25.2%) were current smokers and the average age for beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
3
12
0
1
Order By: Relevance
“…The percentage of smokers in this study (15.5%) is lower than those obtained in general students by the University of Valencia (24.83%) (37) , University of Barcelona (23.4%) (38) , University of Vigo (31.7%) (15) , University of Leon (29.3%) (39) , and University of Texas (26.2%) (40) . It is also lower than those obtained in nursing students from the University of Lima (Peru) (17%) (41) , Australia (21%) (42) , Turkey (22.7%) (43) and (25.2%) (44) , Barcelona (35.1%) (38) , and University of Chile (23.7%) (22) .…”
Section: Discussionmentioning
confidence: 70%
“…The percentage of smokers in this study (15.5%) is lower than those obtained in general students by the University of Valencia (24.83%) (37) , University of Barcelona (23.4%) (38) , University of Vigo (31.7%) (15) , University of Leon (29.3%) (39) , and University of Texas (26.2%) (40) . It is also lower than those obtained in nursing students from the University of Lima (Peru) (17%) (41) , Australia (21%) (42) , Turkey (22.7%) (43) and (25.2%) (44) , Barcelona (35.1%) (38) , and University of Chile (23.7%) (22) .…”
Section: Discussionmentioning
confidence: 70%
“…The majority of these deaths are in low-and middle-income countries. In addition, over the next years, it is predicted that this discrepancy will widen [1,2,3,4]. If tobacco uses trends remain as at present, by the year 2030, tobacco will cause the deaths of more than 8 million people worldwide every year.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were also conducted to detect cigarette use frequency among college students. It was found that the smoking rate ranges between 7.8% and 58.0% among college students [1,3,12,13]. Even though tobacco use is significant for each individual in society, it is more important for some groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations